Scoliosis in Shprintzen–Goldberg Syndrome - Hiromitsu Takano; Ikuho Yonezawa; Takatoshi Okuda; Hajime Kajihara; Kazuo Kaneko (Case Reports in Orthopedics)
We report a case of scoliosis in a 12-year-old girl with Shprintzen–Goldberg syndrome. She was diagnosed with Shprintzen–Goldberg syndrome at birth. She was hospitalized for a surgical treatment because scoliosis gradually progressed. Preoperative X-ray confirmed 80° symptomatic scoliosis in T10–L5. Posterior correction and fusion were performed, and postoperative X-ray showed a correction to 43°in T10-L5. Limited subcutaneous tissues and fragile bones must be considered when selecting the appropriate surgical method. Accurate placement of a screw into thin pedicle is essential to obtain sufficient correction and fusion. The use of a navigation system is recommended.